Countdown city - Winters, Ben H. (Winters, Ben H. Last policeman ;, 2013)
Set three months before a deadly asteroid is due to hit Earth, this Last Policeman sequel chronicles the further adventures of Hank Palace. The Concord Police Department is now operating under the auspices of the U.S. Justice Department, and Hank is out of a job-until he's hired by a business tycoon to help find the man's estranged son. It isn't long before Hank's missing-person case turns into a murder investigation.